Case report: “Proust phenomenon” after right posterior cerebral artery occlusion - De Beukelaer, Sophie; Sokolov, A. A.; Müri, R. M. (Frontiers in Neurology, 2023)
Odors evoking vivid and intensely felt autobiographical memories are known as the “Proust phenomenon,” delineating the particularity of olfaction in being more effective with eliciting emotional memories than other sensory modalities. The phenomenon has been described extensively in healthy participants as well as in patients during pre-epilepsy surgery evaluation after focal stimulation of the amygdalae and post-traumatic stress disorder (PTSD). In this study, we provide the inaugural description of aversive odor-evoked autobiographical memories after stroke in the right hippocampal, parahippocampal, and thalamic nuclei. As potential underlying neural signatures of the phenomenon, we discuss the disinhibition of limbic circuits and impaired communication between the major networks, such as saliency, central executive, and default mode network.